Religiosity as a buffer against suicidal ideation: a comparison between Christian and Muslim-Arab adolescents - Kakounda Muallem, Helen (Mental health, religion & culture, 2015)
The majority of existing studies on the impact of religious beliefs on adolescents’ suicidal ideation have been conducted among Christians living in Western countries. This study explored the association between religious beliefs and suicidal thoughts among Muslim and Christian adolescents from the Arab minority population of the State of Israel. An estimated 219 late-adolescents participated in this study, including 110 Muslims and 99 Christians, with the same proportion of boys and girls. Participants completed questionnaires on reasons for living, suicidal ideation and religiosity. A significant negative correlation (r = −.33) was found between level of religiosity and suicidal ideation, but only among the Christian adolescents. Religious devoutness may not be a universal buffer against suicidal ideation, across different religions.